CD4+T-cells create a stable mechanical environment for force-sensitive TCR:pMHC interactions - Lukas Schrangl; Florian Kellner; René Platzer; Vanessa Mühlgrabner; Paul Hubinger; Josephine Wieland; Reinhard Obst; José L. Toca-Herrera; Johannes B. Huppa; Gerhard J. Schütz; Janett Göhring (Nature Communications)
Abstract Mechanical forces acting on ligand-engaged T-cell receptors (TCR) have previously been implicated in T-cell antigen recognition and ligand discrimination, yet their magnitude, frequency, and impact remain unclear. Here, we quantitatively assess forces across various TCR:pMHC pairs with different bond lifetimes at single-molecule resolution, both before and during T-cell activation, on platforms that either include or exclude tangential force registration. For this purpose, we use glass-supported lipid bilayers presenting pMHC conjugated to a molecular force sensor unit at its base, adhesion factors and costimulatory molecules to the approaching T-cells. Our results imply that CD4 + T-cell TCRs experience significantly lower forces than previously estimated, with only a small fraction of ligand-engaged TCRs being subjected to these forces during antigen scanning. These rare and minute mechanical forces do not impact the global lifetime distribution of the TCR:ligand bond. We propose that the immunological synapse is created as biophysically stable environment to prevent pulling forces from disturbing antigen recognition.